Energy savings in the combustion based process heating in industrial sector - Hasanuzzaman, Md.; Abd Rahim, Nasrudin; Hosenuzzaman, Md.; Abdul Hakim, Saidur Rahman; Mahbubul Islam, Mohammed; Rashid, Muhammad Mahbubur (Elsevier, 2012)
Energy efficiency and savings strategies in the combustion based industrial process heating has been reviewed comprehensively and presented in this paper. This work compiles latest literatures in terms of thesis, journal articles, conference proceedings, web materials, reports, books, handbooks on industrial process heating systems in the industrial sector. Different types of equipment used (i.e., recuperator, regenerators, heat wheels, heat pipes, economizers, etc.) and energy savings are reviewed in various industrial processes heating. Based on the review results, it is found that significant amounts of energy could be saved by using heat recovery system in the industrial process heating. By using recuperator up to 25% energy can be saved in the furnace. In the case of boiler, by using economizers 10% to 20% energy can be saved. Economic analysis shows that the payback period of recuperator and economizer are normally less than 2 years. It is also found that the payback period is lower when operating hour is comparatively high.